Produção de mudas de espécies florestais de restinga, com base em estudos florísticos e fitossociológicos, visando a recuperação de áreas degradadas, em Ilha Comprida - SP - Carrasco, Pablo Garcia [UNESP] (2003)
The sandbank forests, expression used in this work to designate the forest formations that grow on the coastal sandy plain, possess internal structural heterogeneity and are constituted by vegetation mosaics, being threatened by the building speculation, selective retreat of biological resources and mining activities. The production of native regional forest seedlings, with base on floristic and phytosociological studies, seeking the recovery of degraded areas, in Ilha Comprida - São Paulo State - Brasil, was the aim of this paper. They where studied four areas of 1ha each, by using the method of contiguous portions, becoming evident the presence of 106 native forest species (of wide geographical distribution) and 6 exotic species, being the family Myrtaceae the most representative. There were 23 common species to the four areas. The sampling sufficiency was reached in an area of 70m X 70m for those forest formations. Were registered the phytosociological parameters of 256 individuals for area, by applying the method of the point centered quarter, as well as collected soil samples, being submitted to the physical and chemical analyses. The four disturbed forest formations presented small structural complexity and low specific diversity, with small number of species being represented by many individuals. The soils were poor in nutrients and organic matter, with low fertility and high tenors of aluminum. The forest formations are similar to the ones of Cardoso's Island (São Paulo) and of Mel Island (Paraná - Brasil). In an area degraded by mining of sand, the planting of seedlings occurred directly in the sandy soil and in holes with addition of 50% of peat. During the 175 days of evaluation, the growth gains in height was not significant, being observed the mortality of 23.8% of the seedlings implanted in the soil with peat and 50.4% of the one of the sandy soil. The peat addition, although insufficient in nutrients, increased...